PENGARUH PEMBERIAN POC DAUN LAMTORO DAN KOTORAN AYAM TERHADAP PERTUMBUHAN TANAMAN TOMAT (Solanum Lycopersicum) - Puja Irawan; Dini Hariyati Adam; Novilda Elizabeth Mustamu; Badrul Ainy Dalimunthe (Fakultas Pertanian, Universitas Janabadra, 2023)
Tomato as a horticultural commodity is a source of vitamins and minerals which are very beneficial for the fulfillment of nutrition in the human body, ascorbic acid and carotene, which are contained in tomatoes, are a very important source of substances and can increase body activity. This research was carried out at Manahan Huta Village. Godang Sungai right District, Labuhan Batu Selatan Regency in January-March 2023. The research design was a randomized block design (RAK) consisting of 2 factors, namely the first factor was POC lamtoro leaves and the second factor was chicken manure with 3 replications so that several experiments were obtained, namely namely: L0 = (Control), L1 = (100 ml liquid fertilizer + 900 ml/L water), L2 = (200 ml liquid fertilizer + 800 ml/L water), L3 = (300 ml liquid fertilizer + 700 ml/L water). The second factor was the concentration of chicken manure application (A) with 3 levels, namely: A0 = (Control), A1 = 500 gr/plant, A2 = 1000 gr/plant. The parameters observed were the growth of tomato plants such as plant height, number of leaves and stem diameter. The data collected was then analyzed for variance at the 5% level, and further tests were carried out using Duncan's test or (DMRT) to compare the two treatment means. The results of the analysis of variance showed that there was an interaction between POC administration of lamtoro leaves and chicken manure on plant height parameters but there was no interaction on stem diameter and number of leaves. For the POC dosing factor of lamtoro leaves, the results of variance had a very significant effect on plant height, number of leaves, and stem diameter. While the factor of giving chicken manure showed a highly significant different effect only on plant height. Keywords: Poc lamtoro leaves, chicken manure, tomato plants (Solanum Lycopersicum) INTISARITomat sebagai komoditi hortikultura merupakan sumber vitamin dan mineral yang sangat bermanfaat bagi pemenuhan gizi dalam tubuh manusia, zat asam askorbat dan karoten, yang terkandung dalam tomat, merupakan sumber zat yang sangat penting dan dapat meningkatkan aktivitas tubuh.Penelitian ini dilaksanakan di janji Manahan Desa Huta Godang Kecamatan sungai kanan Kabupaten Labuhan Batu Selatan pada bulan januari-Maret 2023. Rancangan percobaan penelitian rancangan acak kelompok (RAK) yang terdiri dari 2 Faktor yaitu faktor pertama POC daun lamtoro dan faktor kedua pupuk kotoran ayam dengan 3 kali ulangan sehingga diadapatkan beberapa percobaan yaitu yaitu: L0 = (Kontrol),L1 = (100 ml pupuk cair + 900 ml/L air), L2 = (200 ml pupuk cair + 800 ml/L air), L3 = (300 ml pupuk cair + 700 ml/L air). Faktor kedua adalah konsentrasi pemberian pupuk kotoran Ayam (A) dengan 3 taraf yaitu : A0 = (Kontrol), A1 = 500 gr/tanaman, A2 =1000 gr/ tanaman .Adapun Parameter yang diamati yaitu pertumbuhan tanaman tomat seperti tinggi tanaman, jumlah daun dan diameter batang. Data yang dikumpulkan kemudian di analisis sidik ragam pada taraf 5 %, dan dilakukan uji lanjut menggunakan uji Duncan atau (DMRT) untuk membandingkan dua rataan perlakuan. Hasil analisis sidik ragam bahwa terdapat interaksi pemberian POC daun lamtoro dan kotoran ayam pada parameter tinggi tanaman tetapi pada diameter batang dan jumlah daun tidak terdapat interaksi. Untuk faktor pemberian dosis POC daun lamtoro memberikan hasil sidik ragam berpengaruh sangat nyata terhadap tinggi tanaman, jumlah daun, dan diameter batang. Sedangkan faktor pemberian pupuk kandang ayam menunjukkan pengaruh tidak berbeda nyata hanya terhadap tinggi tanaman. Kata Kunci: Poc daun lamtoro , kotoran ayam, tanaman tomat (Solanum Lycopersicum)